Prevalence and co morbidity of adult adhd in psychiatric outpatient admissions - Vidaurri Duran, Santiago; Fıstıkçı, Nurhan; Keyvan, A.; Bilici, Mustafa (Elsevier France-Editions Scientifiques Medicales Elsevier, 2013)
Aim: In the present study, the prevalence of Attention Deficit Hyperactivity Disorder (ADHD) in adult psychiatric outpatients was investigated. Moreover, co morbid psychiatric diagnoses in adults with ADHD were determined. Patients with and without co morbid ADHD were compared regarding axis I-II co morbidity and socio-demographic characteristics. Method: The current study included 246 patients admitted for the first time to Numune Hospital psychiatric outpatient clinic in a four months period where they were evaluated for adult ADHD. Diagnosis of ADHD was made by evaluating symptoms of childhood via WURS scale, Turgay's adult ADD / ADHD evaluation scale. For the exact diagnosis DSM-IV criteria were applied to the patients who exceeded the cut of points of both above-mentioned scales. To assess the presence of psychiatric co morbidity a structured clinical interview (SCID-I and II) were applied. Socio demographic characteristics of patients were determined with a semi-structured form. In addition, to grade general psychopathology, Symptom Check List (SCL-90-R), Beck Depression Inventory (BDI) were given. Results: Prevalence of ADHD in adult psychiatric clinic was 15.9%. Adults with ADHD usually referred due to co morbid psychiatric problems. It was determined that they had deficits in education and social functions. Substance abuse and suicide were among the most prevalent psychiatric problems. Conclusion: ADHD was common in adult psychiatric outpatients and axis I-II co morbidity was highly prevalent among these patients.
WOS: 000335460600354
Keywords: Prevalence and Co Morbidity; Adult Adhd in Psychiatric; Outpatient Admissions